2022
DOI: 10.3389/fnmol.2021.785938
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Reveals the Dynamic Pathophysiology Across Different Stages in a Rat Model of Severe Traumatic Brain Injury

Abstract: BackgroundSevere traumatic brain injury (TBI) has become a global health problem and causes a vast worldwide societal burden. However, distinct mechanisms between acute and subacute stages have not been systemically revealed. The present study aimed to identify differentially expressed proteins in severe TBI from the acute to subacute phase.MethodsSixty Sprague Dawley (SD) rats were randomly divided into sham surgery and model groups. The severe TBI models were induced by the controlled cortical impact (CCI) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 81 publications
(96 reference statements)
2
4
0
Order By: Relevance
“…The staining results suggested that the level of microglia activation was markedly elevated in the hippocampus of rats in the TBI group when compared with the sham group. Through immunofluorescence staining analysis, Luo et al [52] also found that the number of microglia was significantly increased in the hippocampus during the subacute phase of TBI, which was consistent with our results. Similarly, the immune-related DEGs identified by bioinformatic analyses were significantly enriched in BP terms associated with the activation of microglia and macrophages.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The staining results suggested that the level of microglia activation was markedly elevated in the hippocampus of rats in the TBI group when compared with the sham group. Through immunofluorescence staining analysis, Luo et al [52] also found that the number of microglia was significantly increased in the hippocampus during the subacute phase of TBI, which was consistent with our results. Similarly, the immune-related DEGs identified by bioinformatic analyses were significantly enriched in BP terms associated with the activation of microglia and macrophages.…”
Section: Discussionsupporting
confidence: 92%
“…Current evidence indicates extensive crosstalk between the complement and coagulation systems, which have fundamental clinical implications for inflammation, immunity, and tissue damage [51]. A previous proteomics study suggested that complement and coagulation cascades were activated during the acute and subacute phases of TBI, which was consistent with our findings [52].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Inflammatory proteins are typically secreted from microglia to act upon other cells such as neurons and astrocytes (reviewed in Matejuk & Ransohoff, 2020 ; reviewed in Gao et al, 2013 ). Other proteomic studies post‐TBI use whole brain homogenate which contains extracellular components such as effector proteins (Abu Hamdeh et al, 2018 ; Luo et al, 2021 ; Zhang et al, 2021 ). In this study, we isolated microglia from whole brain homogenate, thus, we cannot detect proteins that have been secreted from microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Oxygen transport and acute phase response may be the focus of further research on TBI in the future. Luo et al (2021) combined bioinformatics techniques to discover that in the acute phase of sTBI, in addition to platelet activation and neural‐related pathways, endocrine‐related pathways also undergo changes, including gastric acid secretion, thyroid hormone synthesis, and insulin secretion. This provides proteomic clues for the different pathogenesis of sTBI in the acute and subacute phases and also provides potential signaling pathways and targets for future research.…”
Section: The Application Of Proteomics In Tbimentioning
confidence: 99%